Vestibular migraine screening in a migraine‐diagnosed patient population, and assessment of vestibulocochlear function. (1st August 2016) - Yollu, U.; Uluduz, D.U.; Yilmaz, M.; Yener, H.M.; Akil, F.; Kuzu, B.; Kara, E.; Hayir, D.; Ceylan, D.; Korkut, N.
Abstract : Objective: The primary aim of this study is to do a vestibular migraine scan in a population of patients with migraine diagnosis using the most recent standardized diagnosis criterion which is International Classification of Headache Disorders (ICHD) 3 Beta and to identify the epidemiological data. The second part of the study involves performing several vestibulocochlear tests on patients who received vestibular migraine (VM) diagnosis to collect data that may be important for diagnostic purposes by comparing the patients with normal population when necessary. Design: Blind, cross‐sectional study. Setting: Tertiary referral hospital. Participants: One hundred patients were scanned for VM using ICHD 3 Beta guideline. Main Outcome Measures: In order to evaluate the vestibulocochlear functions of the patients with VM diagnosis, audiometry, tympanometry, electrocochleography (EcochG), computerized dynamic posturography (CDP) and video head impulse test (vHIT) were performed; besides in order to evaluate the significance of the results of the tests, second group was formed with migraine patients without any vestibular complaints and control group was formed from healthy population when needed. Results: VM prevalence was determined to be 21% in migraine patients which is much higher than stated in current literature. No significant difference was observed between migraine and VM patients with respect to audiometric and tympanometric measurements. According to the CDP results, balance defects were present in VM patients, even during attack‐free periods. EcochG data suggests average SP/AP scores of VM patients are significantly higher than migraine patients. Furthermore, the number of patients who exceeded a limit value of 0.4 or 0.5 in SP/AP scores was significantly higher in VM patients than in migraine patients. Also vHIT results show that nearly half the VM patients, which is a significant ratio, have saccadic movements and this is thought to be compatible with peripheral vestibular involvement. Conclusion: Our results suggest VM disease is more common than previously thought. We believe that further EcochG‐based studies would shed light on the controversial topic on the intersection and disjunction sets of MD and VM diseases. Although the results of the present study are compatible with peripheral vestibular effects, it is not possible to rule out another central mechanism at some other level.